The Effect of Internal Control Effectiveness, Compensation Suitability, Management Morality, and Unethical Behavior against the tendency of Accounting Fraud - Septiana, Vira; Bambang, Bambang; Waskito, Iman (Formosa Journal of Applied Sciences, 2024)
This study aims to test and determine the effect of the role of internal control, compensation suitability, management morality, and unethical behavior on the tendency of accounting fraud. The collection technique used in this study was a questionnaire. The questionnaire was distributed to 78 cooperatives in Praya District. The sample was determined by purposive sampling technique. This research is included in quantitative research. Data analysis used Statistical Product and Service Sollution (SPSS) analysis using SPSS software version 27.0 for windows. The result of this study indicate that internal control, compensation suitability, management morality, and unethical behavior have no effect on the tendency of accounting fraud.